Oral Rehydration Therapy in Young Infants less than 3 Months with Acute Diarrhoea and Modeate Dehydration - Sunoto Sunoto; Suharyono Suharyono; Aswitha D. Budiarso; Adnan S. Wiharta (Paediatrica Indonesiana, 1988)
Oral rehydration therapy (ORT) as an appropriate technology in the treatment of acute diarrhoeal diseases (ADD) has been accepted throughout the world. It has been proved that besides lifesaving, ORT has reduced about 70-80% of the use of intravenous solution and average cost of the treatment of ADD. If there is still problem, question or doubtfulness, is the use of WHO ORS in full concentration for the neonates and young infants less than 3 months of age. During one-year period it has been treated 72 cases of ADD in young infants less than 3 months of age with moderate dehydration. They were divided into 3 groups. The first group was treated with 100 mil kg bw of fluid consisting oftwothirds as WHO ORS in full concentration for 4 hours period and the rest, one-third, was given as plain water for 2 hours period. The second group was treated with kristalyte with the Na concentration of 51 mEq/L and the third group was treated with intravenous Ringer's lactate for 6 hours period. After the end of the study only 18 patients in each group could be matched and evaluated. From clinical observation and laboratory examinations, the result of the treatment in general, statistically shows no significant difference. Diarrhoea and vomiting stopped in all groups on the second day of treatment. Hyponatremia which occurred in 3 patients in Group I and 2 patients each in Group II and III improved after 6 hours of treatment. Acidosis was corrected in all of the treatment groups in 6 hours period. Weight gain up to 6-9% of body weight on admission was achieved after 6 hours of treatment in all groups. No complication of hypernatremia, convulsion nor hypoglycaemia in all the treatment group. From this study it could be concluded that WHO ORS is quite safe and effective as ORS with low sodium concentration and intravenous treatment, as far as it is given slowly, little by little with a strict supervision.